Adequate Prenatal Care: An Integrative Review. (24th December 2022) - Michel, Alexandra; Fontenot, Holly
Abstract : Introduction: Prenatal care (PNC) is a core element of preventive care and is vital in identifying and managing conditions that can put the pregnant person and the fetus at risk. National and international guidelines differ in what is considered adequate or quality PNC. Indices of care adequacy rely only on number of attended PNC visits without regard to factors that affect a patient's ability to obtain care or the quality of the care received. This integrative review explored stakeholders' perceptions of adequate and quality PNC. Methods: Three electronic databases, CINAHL, PubMed, and Web of Science, were searched to identify original research articles published between 2012 and April 2022. Studies conducted in the United States, published in a peer‐reviewed journal, and having a primary focus on the components of adequate or quality PNC were included. The quality of included studies was assessed via the Quality Assessment Tool for Studies with Diverse Designs. Results: Thirteen articles met inclusion criteria. The concepts of adequate or quality PNC were not well defined in the literature. Studies revealed a variety of approaches to assessing individual components of PNC with at times conflicting results of what adequate or quality PNC is. Viewpoints regarding adequacy or quality of PNC were limited by the perceptions and interpretations of individual stakeholders, who included researchers, public health officials, insurers, health care providers, and patients. Discussion: Ideas of how to redesign PNC were affected by study setting and stakeholders, as well as the emergence and integration of telehealth into PNC delivery. This review is a first step in identifying the gap in the research literature regarding how these concepts are defined and measured. Future research is needed to identify the relevant components of PNC that are necessary to reach consensus definitions of both adequacy and quality of PNC.